Research and application of intelligent diagnosis and treatment engineering bacteria - Na Zhao; Junwei Chen; Jingtian Shi; Yan Gao; Lijing Li; Liyun Dong (Frontiers in Bioengineering and Biotechnology)
For over a century, scientists have been harnessing the therapeutic potential of bacteria in treating diseases. The advent of synthetic biology in recent years has propelled the development of genetically engineered bacteria with enhanced intelligence. These bacteria can autonomously detect environmental cues and relay them to pivotal promoters, leading to the expression of functional proteins. By utilizing modular components, they are capable of executing a range of functions, including sensing, transmitting, and outputting signals. Based on these principles, a series of intelligent diagnostic and therapeutic engineered bacteria have emerged. These bacteria are capable of targeting diseased sites, sensing disease-specific signals, and producing reporter and therapeutic drugs. Furthermore, the integration of intelligent diagnostic and therapeutic engineered bacteria with advanced technologies such as artificial intelligence, nanomaterials, and optics has paved the way for diverse clinical applications. Three critical stages are explored in this article, which include the selection of strains, the design of biosensing systems, and the planning of release strategies. The application of intelligent diagnosis and treatment engineering bacteria in metabolic diseases, inflammatory diseases, tumors and infectious diseases is reviewed.